AKUNTABILITAS PENGELOLAAN DANA DESA BERBASIS SYARIAH ENTERPRISE THEORY - Ida Ariani; Lince Bulutoding; Namla Elfa Syariati (ISAFIR: Islamic Accounting and Finance Review, 2022)
The purpose of this study is to determine the condition of village fund management, and to examine accountability in the management of village funds based on sharia enterprise theory to realize good governance in Buntu Sarong Village. This research is a qualitative research with a phenomenological approach. The source of the data used is primary data obtained directly from informants through interview and observation methods, while secondary data is obtained from journals and books. -applicable rules. This is evidenced by the management of village funds starting with the village development planning meeting which involves community participation in the implementation of village activities. In addition, the Buntu Sarong Village government also instills spiritual values ​​in the management of village funds and realizes accountability vertically to Allah SWT, and horizontally to humans and nature in accordance with the principles of sharia enterprise theory.